Gravity Modeling: International Trade and Innovations - Dushko Josheski; Risto Fotov (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
In this paper issue of gravity modeling in international trade has been investigated. Standard gravity equation augmented with other variables to control for transportation cost, whether trade partners are neighbors and whether country is landlocked, or countries participants in trade have had colonial history together. Also in our model we control whether traded commodities are homogenous, differentiated or high tech , as well referenced. Variable to denote technology are :TAI index, which stands for technological achievement index, also variables for creation and diffusion of technology , as measured by the number of patents from the residents and royalty and license fees receipts, by the foreign citizens. Results are as expected and the show that trade is highly dependent on the exporters and importers levels of technology
Keywords: F11; F41; 330; gravity model; bilateral trade